The impacts of bovine milk, soy beverage, or almond beverage on the growing rat microbiome - Cakebread, Julie; Wallace, Olivia A.M.; Henderson, Harold; Jauregui, Ruy; Young, Wayne; Hodgkinson, Alison (PeerJ, 2022)
Background Milk, the first food of mammals, helps to establish a baseline gut microbiota. In humans, milk and milk products are consumed beyond infancy, providing comprehensive nutritional value. Non-dairy beverages, produced from plant, are increasingly popular as alternatives to dairy milk. The nutritive value of some plant-based products continues to be debated, whilst investigations into impacts on the microbiome are rare. The aim of this study was to compare the impact of bovine milk, soy and almond beverages on the rat gut microbiome. We previously showed soy and milk supplemented rats had similar bone density whereas the almond supplemented group had compromised bone health. There is an established link between bone health and the microbiota, leading us to hypothesise that the microbiota of groups supplemented with soy and milk would be somewhat similar, whilst almond supplementation would be different. Methods Three-week-old male Sprague Dawley rats were randomly assigned to five groups (n = 10/group) and fed ad libitum for four weeks. Two control groups were fed either standard diet (AIN-93G food) or AIN-93G amino acids (AA, containing amino acids equivalent to casein but with no intact protein) and with water provided ad libitum. Three treatment groups were fed AIN-93G AA and supplemented with either bovine ultra-heat treatment (UHT) milk or soy or almond UHT beverages as their sole liquid source. At trial end, DNA was extracted from caecum contents, and microbial abundance and diversity assessed using high throughput sequencing of the V3 to V4 variable regions of the 16S ribosomal RNA gene. Results Almost all phyla (91%) differed significantly (FDR < 0.05) in relative abundance according to treatment and there were distinct differences seen in community structure between treatment groups at this level. At family level, forty taxa showed significantly different relative abundance (FDR < 0.05). Bacteroidetes (Bacteroidaceae) and Firmicutes populations (Lactobacillaceae, Clostridiaceae and Peptostreptococcaceae) increased in relative abundance in the AA almond supplemented group. Supplementation with milk resulted in increased abundance of Actinobacteria (Coriobacteriaceae and Bifidobacteriaceae) compared with other groups. Soy supplementation increased abundance of some Firmicutes (Lactobacilliaceae) but not Actinobacteria, as previously reported by others. Conclusion Supplementation with milk or plant-based drinks has broad impacts on the intestinal microbiome of young rats. Changes induced by cow milk were generally in line with previous reports showing increased relative abundance of Bifidobacteriacea, whilst soy and almond beverage did not. Changes induced by soy and almond drink supplementation were in taxa commonly associated with carbohydrate utilisation. This research provides new insight into effects on the microbiome of three commercially available products marketed for similar uses.
Keywords: Bovine milk; Soy drink; Almond drink; Amino acid diet; Microbiome; Growing rat